A Two Stage Solution Procedure for the Lock Box Location Problem - Fielitz, Bruce D.; White, Daniel L. (Management Science, 1981)
New lock box solution techniques have recently been suggested by Stone and Nauss-Markland. This paper briefly discusses these new methodologies and shows how the algorithms can be combined into a third solution procedure which exploits the computational efficiency of the Stone heuristic and retains the optimizing property of the Nauss-Markland algorithm.